Vegetation and location of water inflow affect evaporation in a subtropical wetland as indicated by the deuterium excess method. Issue 4 (4th March 2019) - Zhai, Lu; Wang, Xin; Wang, Peng; Miralles‐Wilhelm, Fernando; Sternberg, Leonel da Silveira Lobo
Abstract: Evaporation represents a principal form of water loss from water bodies, but quantifying evaporation with transpiring vegetation is challenging, owing to the difficulties in disentangling evaporation from transpiration. As the two processes have different effects on water isotope signatures (i.e., oxygen and hydrogen stable isotope ratios expressed by δ 18 O and δ 2 H), we used both the δ 18 O and δ 2 H values of water samples to calculate their deuterium excess ( d ) values, which are proportionate to fraction of evaporation loss ( E f ) of water being sampled. Comparing with a single isotope method, the d method holds the advantage that it does not require knowledge of the initial isotope ratios of source water. Limitations of the d method, for example, effects of prior‐evaporation of water before entering water bodies, can be checked and corrected. The sampling locations throughout our study site differed in vegetation coverage, water depth, and distance to water inflow (or discharge gate of water inflow), which are three important factors in water management. This sampling design offered us a unique opportunity to quantify the influences of the above three factors on E f . We found the following: (1) There was a spatiotemporal pattern in δ 18 O distribution. (2) The E f was negatively related to the vegetation coverage, positively related to distance to the water source inflow but nonsignificantly related to water depth. Therefore, vegetation and distance to the water inflow are two important considerations for the control of evaporative water loss, and evaporation calculated by the d method can lead to more informed water management.